SWOT Analysis of Declining Accreditation Status of Kindergarten Institutions - Milu Khoirunisa; Edi Waluyo (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
Accreditation is a crucial indicator for evaluating the quality of early childhood education (ECE) institutions. A decline in accreditation status reflects challenges in school management. This study aims to analyze the factors influencing the declining accreditation of kindergartens in Magelang Regency through a SWOT analysis. The research employed a qualitative approach using observations, interviews, and primary data collected from teachers and principals of 10 kindergartens that experienced a decrease in accreditation, as well as secondary data from assessors and the local education office. The findings reveal that the main strength lies in the collaboration among teachers, principals, students, and parents in supporting school activities. The major weaknesses include teachers’ limited skills in information technology, inadequate documentation of learning activities, and insufficient mastery of learning concepts. Opportunities arise from government support and parental involvement, while threats stem from competition with newly established schools and parents’ low awareness of the importance of early childhood education. In conclusion, weaknesses and threats are more dominant in contributing to the decline in accreditation scores. Therefore, improving teachers’ competencies through training, strengthening parental engagement, and optimizing government support are crucial strategies to enhance the quality of ECE institutions.